The Relevance of Philosophy to the Practice of Educational Administration - Hasnah Faizah; Siti Alfathia Yusri; Selly Pratiwi; Widya Sary (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
as a process of managing all components of education so that they run in a directed, orderly, and coordinated manner. However, what often occurs in the field, educational administration does not always run in accordance with the principles of efficiency, justice, and transparency. Several forms of damage or problems often arise due to weak management, a lack of understanding of the philosophical values ​​​​of education, and low integrity in the management of educational institutions, which also have a direct impact on the decline in the quality of education and the failure to achieve national education goals. Philosophy plays a major role in educational administration, serving as a foundation for thought, ethical guidelines, and determinants of direction at every stage of educational management. Philosophy helps educational managers to think rationally, critically, and reflectively in facing various problems, so that decisions taken are not merely technical, but also based on considerations of values ​​​​and justice. This study aims to understand the relationship between philosophical administration values ​​​and educational practices in the context of decision-making. This study uses a qualitative approach, where data collection is carried out through a literature review derived from scientific articles relevant to the research topic. The study has shown that philosophical values ​​play a significant role in shaping ethical principles in educational administration. The conclusion that can be given is that the integration between philosophy and educational administration can strengthen the moral basis and direction of the goals of educational institutions.